Using bivariate latent basis growth curve analysis to better understand treatment outcome in youth with anorexia nervosa. (25th April 2018) - Byrne, Catherine E.; Wonderlich, Joseph A.; Curby, Timothy; Fischer, Sarah; Lock, James; Le Grange, Daniel
Abstract: Objective: This study explored the relation between eating‐related obsessionality and weight restoration utilizing bivariate latent basis growth curve modelling. Eating‐related obsessionality is a moderator of treatment outcome for adolescents with anorexia nervosa (AN). This study examined the degree to which the rate of change in eating‐related obsessionality was associated with the rate of change in weight over time in family‐based treatment (FBT) and individual therapy for AN. Method: Data were drawn from a 2‐site randomized controlled trial that compared FBT and adolescent focused therapy for AN. Bivariate latent basis growth curves were used to examine the differences of the relations between trajectories of body weight and symptoms associated with eating and weight obsessionality. Results: In the FBT group, the slope of eating‐related obsessionality scores and the slope of weight were significantly (negatively) correlated. This finding indicates that a decrease in overall eating‐relating obsessionality is significantly associated with an increase in weight for individuals who received FBT. However, there was no relation between change in obsessionality scores and change in weight in the adolescent focused therapy group. Discussion: Results suggest that FBT has a specific impact on both weight gain and obsessive compulsive behaviour that is distinct from individual therapy.